KEKEP Ibu Motivator Empowerment Program with a Digital Handbook as an Effort to Prevent Stunting - Intan Putri; Esi Putri Silmina; Ririn Wahyu Hidayati (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Nutritional Status of Toddlers in 2022 at Puskesmas (primary health center) Kasihan 1 revealed 79 cases of short toddlers (2.9%). Although this number decreased from the previous year which reached 4.6%, in absolute terms the incidence of stunting is still quite high. The handling of stunting has so far been carried out by all stakeholders, namely from the BKKN, the Head of Service to the village level. Meanwhile, the role of Puskesmas is in the form of assistance and direct intervention in cases of stunting. However, the combination of all stakeholders makes it difficult to find a comprehensive program for stunting prevention. KEKEP Ibu (Mothers Support Group Class) Motivator can be an extension of Puskesmas by providing direct CIE (Communication, Information, and Education) to the community. Two main problems are found, namely: Health service programs and Information Technology Approaches. The priority problems encountered are (1) Health services and the lack of nutritional program aids at puskesmas; (2) There are KEKEP Ibu motivators who do not have skills in comprehensive stunting prevention; (3) There is no digital-based media as a tool for providing CIE. This Community Service Activity aims to help empower KEKEP Ibu Motivators in a comprehensive stunting prevention effort by procuring an assistive tool in the form of a KEKEP Ibu digital motivator handbook and service model with participatory learning and action. The first stage of the assessment was to collect knowledge of KEKEP Ibu Motivator about stunting prevention. Stage two was planning and development planning and preparation for the implementation of the empowerment program and making IEC tools in the form of digital handbooks. Stage three was implementing a mini-workshop in introducing a stunting prevention program, training on making complementary food menus, and CIE simulation. Stage four was the evaluation of re-collecting the knowledge of KEKEP Ibu motivator about stunting prevention. The results of this activity showed that the level of knowledge of KEKEP Ibu motivators in the low category decreased from the previous 43 people (84.3%) to 10 people (19.6%) while the knowledge in the high category increased by more than 100%, originally 8 people (15 .6%) to 41 people (80.4%).